Transformasi Hukum Islam di Indonesia: Dari Tradisi Historis Menuju Integrasi Hukum Nasional (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2025)
Indonesia, as a nation with a Muslim-majority population, presents its own dynamics in the development of national law. This article aims to analyze the processes of transformation and integration of Islamic law into Indonesia’s national legal system from both historical and contemporary perspectives. Employing historical, normative, and sociological approaches, this study traces the trajectory of Islamic law from the era of Islamic kingdoms in the archipelago and the colonial period to its institutionalization in the modern national legal framework through regulations such as the 1974 Marriage Law, the Compilation of Islamic Law, and the recognition of Sharia in Aceh. The findings indicate that Islamic law functions not only as a cultural and religious legacy but also as a normative pillar that strengthens the national legal system. Its integration has occurred through legislative channels, the religious court system, and public policies that are harmonized with the values of Pancasila and the Constitution. Nevertheless, this process continues to face challenges, particularly in reconciling Sharia-based norms with principles of human rights and gender equality. This article underscores the need for a contextual fiqh approach and the application of maqāṣid al-sharī‘ah so that Islamic law may serve as an instrument of substantive justice that is adaptable to Indonesia’s legal and social pluralism.